KORELASI MODEL PEMBELAJARAN DENGAN HASIL BELAJAR MAHASISWA PADA PEMBELAJARAN BAHASA PEMROGRAMAN JAVA - Anthony Anggrawan (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
In learning programming languages, students do not always achieve good learning outcomes, even from the results of previous studies indicating the reported failure rate is quite high. Departing from the problem of the high unsuccessful students in learning programming languages, it is necessary to do research to determine the correlation between learning models of programming languages on learning outcomes. By knowing the correlation of learning models to student learning outcomes, it can be revealed which learning model has more dominant contribution to learning outcomes in programming learning, and also the magnitude of the contribution of other factors in influencing learning outcomes outside the learning model. Furthermore, even though previous studies revealed that online learning can replace face-to-face learning, a large number of educational institutions still persist in implementing face-to-face learning models. For this reason, a correlation study between the learning model and student learning outcomes is conducted on face-to-face learning and Java programming online learning. This study found a positive and significant correlation between online learning models and mixed learning on student learning outcomes in learning the Java programming language with a coefficient of determination0.25. So it can be concluded that the variance that occurs in learning outcomes of 25% can be explained in the variables of learning model.In other words, 75% of learning outcomes are influenced not because of the influence of the learning model.